Enhanced gas barrier and thermal properties of polyimide/montmorillonite nanocomposites as a result of "dual‐plane" structure effect. (28th December 2017) - Liu, Yi Wu; Liu, Jun Jie; Ding, Qian; Tan, Jing Hua; Chen, Jun Yi; She, Zhi Hong; Tang, Ao; Zeng, Ke Jian
Abstract : A type of highly exfoliated, dispersed, and oriented organic montmorillonite filled polyimide (DABPI/OMMT) nanocomposites has been prepared successfully via in situ polymerization. Compared with the pristine DABPI, the DABPI/OMMT nanocomposites exhibit much better barrier and thermal performance. The water vapor permeability and oxygen permeability of DABPI/OMMT (5 wt%) are low to 0.31 g mil m −2 day −1 and 0.72 cm 3 mil m −2 day −1, respectively. Meanwhile, its 5% weight‐loss temperature and coefficient of thermal expansion are 568°C and −1.1 ppm K −1, respectively. The results of transmission electron microscopy, 1D and 2D wide angle X‐ray diffractograms, as well as positron annihilation lifetime spectroscopy reveal that the excellent barrier and thermal performance of DABPI/OMMT (5 wt%) are mainly because of the high orientation of OMMT, increased crystallinity and low free volume of DABPI matrix. These are resulted from the "dual‐plane" structure effect, which is the synergistic orientation effect between the rigid planar molecular chains of DABPI and nanoplatelets of OMMT. POLYM. COMPOS., 39:E1725–E1732, 2018. © 2017 Society of Plastics Engineers